Innovation of Edupreneurship-based Science Literacy Module to Increase Independent Dimensions of Elementary School Students - Yuniharto, Bonifatius Sigit; Pardimin; Nisa, Ana Fitrotun (Universitas Pendidikan Ganesha, 2024)
Independent attitude is one aspect of the main goals of education. However, this independent attitude needs special attention, as currently the strawberry generation phenomenon which is characterized by children's low level of independence is widespread including in Indonesia. This research aims to develop innovative a scientific literacy module based on Ajak-Temani-Mandiri learning model integrated with Edupreneurship to increase the independent attitude of elementary school students. This research used Borg & Gall research and development method with stages, namely: research and information collecting; planning; develop preliminary form of product; preliminary field testing; main product revision; main field testing; operational product revision; operational field testing; final product revision; and dissemination & implementation. The subjects in this research were one expert judgment who validated the instrument, two expert judgments as product validators: namely validators of learning resources and materials. Meanwhile, the limited trial subjects for this research were class IV students at SDNS, totaling 21 students, and for the wide trial, class IV students at SDNM1, totaling 56 students. Data collection techniques were carried out using interview, observation and questionnaire techniques. The data analysis technique used qualitative and quantitative descriptive techniques in the form of inferential statistics. The results showed that a scientific literacy module was produced with characteristics in accordance with the stages of Ajak-Temani-Mandiri learning model integrated by edupreneurship which is valid and proven was able to increase students’ independent attitude of elementary school students.